Replacing pharmaceuticals for nutraceuticals in feeding of broilers - Del Carpio Hernández, Sergio Rafael B. (2015)
This research was carried out with the objective of replacing antibiotic growth promoters (AGP) in the diet of broilers by nutraceuticals principles without affecting performance adversely. History has also shown that the use of antibiotics in poultry feeding can be one of the causes of antibiotic - resistance in human beings; due to this, prohibitions to its employment have already been given in Europe, the United States, and Japan. Apparently, such a ban is a matter that is going to be worldwide spread; so we need to research about the national poultry industry to be prepared and because people deserve a quality food. Three hundred one-day-old Cobb chickens of both sexes and homogeneous body weight were used, in a duration of 7 weeks test, in which the following treatments were evaluated: T1 (Traditional Diet without AGP), T2 (Traditional Diet with AGP ), T3 (Nutraceuticals Diet without AGP) and T4 (nutraceuticals Diet, with AGP). Respectively for treatments 1, 2, 3 and 4 the following results were found: Food consumption of 3,507, 3,267, 3,504 and 3,145 kg per chicken per period; the average was 71.6, 66.9, 71.51 and 62.2 g per chicken per day. Weight increase of 2182.8, 1949.6, 2203.5 and 1884 g per chicken per period; on average 44.55, 39.79, 44.97 and 38.45 g per chicken per day. Feed conversion of 1.61, 1.59 and 1.67 1.68 kg of food consumed per kilogram of weight increased. Nutraceuticals principles without AGP increased consumption of food, further weight and more efficient use of food. In terms of biological efficiency, it was determined that the evaluated nutraceutical sources do can replace the AGP; but it is recommended to perform a relevant research to improve the economic value.